EMadrid project: MOOCs and learning analytics - Piedra Pullaguari, N. (2016)
Both, MOOCs and learning analytics, are two emergent topics in the field of educational technology. This paper shows the main contributions of the eMadrid network in these two topics during the last years (2014-2016), as well as the planned future works in the network. The contributions in the field of the MOOCs include the design and authoring of materials, the improvement of the peer review process or experiences about teaching these courses and institutional adoption. The contributions in the field of learning analytics include the inference of higher level information, the development of dashboards, the evaluation of the learning process, or the prediction and clustering. © 2016 IEEE.